2023
DOI: 10.1097/hep.0000000000000322
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant fucosylation sustains the NOTCH and EGFR/NF-κB pathways and has a prognostic value in human intrahepatic cholangiocarcinoma

Abstract: Background and Aims: Intrahepatic cholangiocarcinoma (iCCA) is a lethal malignancy, with increasing incidence worldwide and limited therapeutic options. Aberrant protein glycosylation is a hallmark of cancer. Here, we thoroughly investigated the possible involvement of fucosylation in cholangiocarcinogenesis. Approach and Results: We discovered that the levels of global fucosylation and members of the fucosylation pathway are ubiquitously upregulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…34 Glyco-analytical methodologies including lectin blot, 35 glycan microarray 36 and glycoproteomic analysis 37,38 have been utilized to probe the glycobiology in CCA. In addition, abnormal sialylation, 39 fucosylation 40 and O-linked N-acetylgalactosamine (GalNAc) modi cation (O-GalNAcylation) 41 have also been implicated in prognostic outcome in human cholangiocarcinoma. Changes in O-GlcNAc levels and the cycling enzyme pair OGT/OGA in a myriad of tumor types have also been reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…34 Glyco-analytical methodologies including lectin blot, 35 glycan microarray 36 and glycoproteomic analysis 37,38 have been utilized to probe the glycobiology in CCA. In addition, abnormal sialylation, 39 fucosylation 40 and O-linked N-acetylgalactosamine (GalNAc) modi cation (O-GalNAcylation) 41 have also been implicated in prognostic outcome in human cholangiocarcinoma. Changes in O-GlcNAc levels and the cycling enzyme pair OGT/OGA in a myriad of tumor types have also been reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Glyco-analytical methodologies including lectin blot, [57][58][59] glycan microarray 60 and glycoproteomic analysis [61][62][63][64] have been utilized to probe the glycobiology in CCA. In addition, abnormal sialylation, [65][66][67][68] fucosylation 69,70 and O-linked Nacetylgalactosamine (GalNAc) modification (O-GalNAcylation) 60,[71][72][73] have also been implicated in prognostic outcome in human cholangiocarcinoma. Changes in O-GlcNAc levels and the cycling enzyme pair OGT/OGA in a myriad of tumor types have also been reviewed.…”
Section: Discussionmentioning
confidence: 99%
“… 118 Another study revealed that elevated fucosylation is a hallmark of human iCCA, promoting cell growth and migration by upregulating Notch and EGFR/NF-κB pathways. 119 Simultaneously, the Notch pathway is considered a key indicator of CCA progression and prognosis. 120 , 121 Studies show that Notch1 is upregulated in iCCA, potentially promoting iCCA migration by inducing EMT.…”
Section: The Notch Signaling Pathway and Cancermentioning
confidence: 99%